Hubungan Dukungan Keluarga dengan Kejadian Baby Blues pada Ibu Postpartum di Desa Pulau Terap Tahun 2022 - Ance Siallagan; Helinida Saragih; Ernita Rante; Rosa Desri (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Baby blues is a condition where there is a change in mood in postpartum mothers that occurs every time after the mother gives birth to her baby. Baby blues occur due to several factors, namely internal and external. Symptoms that appear in postpartum mothers can interfere with the mother's ability to carry out roles, one of which is caring for the baby and inhibiting the release of oxytocin which ultimately reduces milk production. Family support is a way to prevent or overcome the increase in psychological disorders felt by postpartum mothers through motivation and enthusiasm in preventing mothers from experiencing postpartum blues. This study aims to determine the relationship between family support and baby blues Incidence on Postpartum Mothers at Pulau Terap Village Kampar Regency Riau Province 2022. This study use a cross sectional design with a total sampling of 46 respondents. The results shows that there is no family support for postpartum mothers as much as 56.5% and postpartum mothers who experienced severe baby blues as much as 45.7%. Data analysis shows that there is a relationship between family support and the incidence of baby blues on postpartum mothers at Pulau Terap Village, Kampar Regency, from the results of the chi square statistical test found p-value = 0.001. It is hoped that further researchers will be able to examine postpartum mothers who are currently experiencing the baby blues, and can implement an intervention in reducing or preventing the baby blues.